PENGARUH PERAWATAN METODE KANGGURU (PMK) DENGAN PENINGKATAN BERAT BADAN PADA BAYI DENGAN BERAT BADAN LAHIR RENDAH (BBLR) DI RSKDIA PERTIWI MAKASSAR - Nur Febrianti; Sri Nala (Stikes Graha Edukasi Makassar, 2019)
Kangaroo method care (PMK) is skin-to-skin contact between mother and baby early, continuously and combined with exclusive breastfeeding. The purpose of this study was to determine the effect of PMK (kangaroo method treatment) on weight gain in babies with low birth weight (LBW) at RSKDIA Pertiwi Makassar. The research design used was a pre-experimental design with a pre-posttest design in one group (One-group pre-post test design), namely research that used one group of subjects and carried out measurements before and after treatment of the subjects. The population was all LBW babies treated at the Pertiwi RSKDIA Makassar nursery, totaling 16 people using a consecutive sampling technique. The results of the study were obtained from 16 respondents where the average weight gain in babies with LBW at Pertiwi Hospital in Makassar, after being given the kangaroo method (PMK) treatment was 2162.50 grams. From the results of data analysis using the Repeated Anovamaka test, significant results were obtained with a value (p=0.000) which means pvalue <? 0.05. It can be concluded that H0 is rejected and Ha is accepted, namely there is an effect of the kangaroo method treatment (PMK) on weight gain in babies with low birth weight (LBW) at RSKDIA Pertiwi Makassar. It is hoped that related agencies will provide PMK training to all nurses in the nursery so that PMK steps can be carried out properly and so that nurses are able to provide health education for mothers who have babies with LBW babies so that PMK can be carried out at home